Media News Framing Analysis: The Urgency of Removing the Nusantara Capital - Putra, Rizali Affandi Priyatama (Edulib, 2022)
This study uses the Framing Analysis Method with a Qualitative Descriptive approach in 4 stages according to Robert N. Entman's theory: Define the Problem, Diagnose Causes, Make a Moral Judgment, and make Treatment Recommendation. What is concluded as the Define Problem is about the Ratification of the Capital Transfer Bill, which was carried out secretly and ratified quickly. Meanwhile, in terms of Diagnose Causes, it is about the massive coverage from media that is against the decision to relocate the capital, such as Tempo. Co, which is quickly responded to by pro-government media, such as Kompas.com. Whereas the Treatment Recommendation refers to the activities of the two media, which reflects an image of democracy, where freedom of expression and freedom of the press is upheld. The media can respond to a phenomenon freely without any intervention, and both have the right to determine their position in addressing the issues of the Archipelago Capital Transfer Project.